Dual nitrogen-sulfur-doping induce microwave absorption and EMI shielding in nanocomposites based on graphene - Elagib, Tienah H.H.; Kabbashi, Nassereldeen A.; Alam, Md Zahangir; Hassan, Elwathig A.M.; Mirghani, Mohamed Elwathig Saeed; Azhari, Nour Hamid Abduelraman (World Scientific, 2023)
Graphene-oxide (GO) is one of the most commonly used carbon nanomaterials in advanced applications such as microwave absorption and EMI shielding, due to various advantages such as ease of synthesis and exfoliation, effective doping capability, and superior composite compatibility. In this study, we used the modified Hummer's method to synthesize GO by exfoliating graphite powder, and a simple hydrothermal approach was employed for elemental doping and GO reduction. As nitrogen-sulfur (N, S) dual-doping precursors, thiourea and l-cysteine amino acids were utilized. The structural features and microporous network structure of GO aerogel foams were investigated. The microwave absorption capabilities of polyethersulfone-based nanocomposite films incorporating the as-produced nitrogen-sulfur enrich reduced GO (NS-rGO) are also explored. According to the physicochemical characterization, the existence of remarkable structural defects with a porous three-dimensional (3D) network was discovered due to heteroatom insertion and hydrothermal doping. Additionally, the dual-doped sample exhibited high Nitrogen and sulfur content of 8.93% and 13.19%, respectively. While NS-rGO possesses a higher conductivity of 174.7μS compared to 12.65μS for GO. The nanocomposites filled with NS-rGO foams demonstrated a high shielding efficiency (SE) of 45dB in the X-band with a filler loading of 0.5wt.%. This high SE arises from dopant heteroatoms and the heterogeneous interface, which induce interface polarization, thereby increasing microwave absorption and dielectric constant. It also results from multi-level reflections caused by the 3D porous structures. These findings offer valuable insights into the functionalization of carbon nanostructures and the development of 3D networks in GO-based functional materials, providing further guidance for engineering high-performance electromagnetic interference shielding materials.